New Paradigm of RegTech for Holding Digital Corporations (HODCs) in Indonesia: From Disruptive to Sustaining Innovation - Airin Liemanto; Sukarmi Sukarmi; Reka Dewantara; Nurul Ula Ulya (Kertha Patrika, 2022)
The digital era demands transformation of all sectors, including the sector of economic law. The concept of economic law that is demanded to transform and transplant itself is the legal concept in the digital founding of companies. Companies no longer possess conventional schemes; they have transformed in terms of management patterns, market reach, and even organizational structure toward digital concepts, and therefore the law must be adaptive with these developments. The research for this article has the objective of forming new legal paradigms in the founding of companies. It takes the form of a normative legal research with usage of the philosophical and statute approaches. The results of the research showed that the adoption of concepts from the New Paradigm Theory of Kuhn requires a new legal paradigm with a new legal regime, because the old legal regime is not adaptive to the new form of companies with the conception of an enterprise form utilizing a technological approach through the aid of Regtech.